ISLAM POPULER DI MEDIA MASSA - Musnur Hery (Millah: Journal of Religious Studies, 2009)
Todays, the power of mass media cannot be avoided. It is able to influence and form the public opinion. The influence is also on various aspects of life, including the people religious life. This religious life has been coloring the mass media. This fact indicates that the religious life may become one of the interesting programs which can be sold and economically valuable. As a result, religion is no longer in the form of preaching and delivering good or bad behaviours. Religion will become more dynamic and flexible. Consequently, the focus is not on the importance of the religion, but on the role and performance of the figures and the relativity of the show. Thus, religion becomes popular. The religion-based drama is conducted by the religious figures and their followers. The use of drama provides that religion is merely a popular show ; therefore it becomes difficult to attain the realities.